2015
DOI: 10.1128/jcm.03233-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Susceptibility of Aspergillus Section Nigri in China: Prevalence of Species and Paradoxical Growth in Response to Echinocandins

Abstract: Molecular identification and in vitro antifungal susceptibility tests of 43Aspergillus section Nigri isolates from China were performed. Aspergillus niger and Aspergillus tubingensis were present in almost equal numbers. All of the isolates had low MIC/ MECs (minimum effective concentrations) for the 7 common antifungals, and a paradoxical effect was observed for the first time in response to caspofungin and micafungin.A spergillus section Nigri, which includes 26 species of black Aspergillus, is important in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Our finding suggests that A. tubingensis isolates are intrinsically resistant to azoles, but this does not depend on exposure to azoles. Several reports from other countries, so far, have supported the idea of less susceptibility in A. tubingensis (6,7,9,21). Considering the lowered azole susceptibilities in A. tubingensis, it must be further stressed that identification of the detailed species causing mycoses is important for appropriate drug therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding suggests that A. tubingensis isolates are intrinsically resistant to azoles, but this does not depend on exposure to azoles. Several reports from other countries, so far, have supported the idea of less susceptibility in A. tubingensis (6,7,9,21). Considering the lowered azole susceptibilities in A. tubingensis, it must be further stressed that identification of the detailed species causing mycoses is important for appropriate drug therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, several reports on the antifungal drug susceptibility of strains of Aspergillus section Nigri have revealed that strains showing higher MICs of itraconazole were often isolated from A. niger and A. tubingensis in a clinical setting as well as from the environment (6)(7)(8)(9). This is suggestive of an intrinsic resistance to itraconazole by these species.…”
mentioning
confidence: 94%
“…and cryptic species within the genus Aspergillus, have been reported as causative agents of aspergillosis worldwide, including China. [16][17][18] The recommended first-line drugs to treat aspergillosis are triazoles. 19 However, triazole-resistant isolates of Aspergillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The management and prophylaxis of aspergillosis is mainly performed using triazole drugs, although longterm therapy and the indiscriminate use of azoles in agriculture have raised concerns about resistance to these compounds (8)(9)(10). In spite of the large number of reports of triazole resistance phenomena worldwide, mainly in Aspergillus fumigatus isolates from environmental and clinical settings (9,10), data on the in vitro antifungal susceptibilities of members of Aspergillus section Nigri are scant and those available show that clinical isolates from different geographical regions exhibited remarkably different azole susceptibilities (5,7,11,12). Azole resistance mechanisms have been described mainly in A. tubingensis (5), the most common being attributed to point mutations in the cyp51A gene encoding the azole target protein (14␣-sterol demethylase [CYP51A]) (9,10).…”
mentioning
confidence: 99%
“…Species belonging to Aspergillus section Nigri have been difficult to classify due to their phenotypic similarities (4), whereas molecular tools such as the sequencing of calmodulin and ␤-tubulin genes have been successfully employed for species identification and discrimination within section Nigri. Molecular data have shown that Aspergillus tubingensis is the species most frequently distributed in various environments (5)(6)(7). The management and prophylaxis of aspergillosis is mainly performed using triazole drugs, although longterm therapy and the indiscriminate use of azoles in agriculture have raised concerns about resistance to these compounds (8)(9)(10).…”
mentioning
confidence: 99%